CO-OPERATORS PERCEPTION TOWARDS COOPERATIVES INVOLVEMENT IN EXTENSION SERVICE DELIVERY IN DELTA STATE, NIGERIA. - Ehiwario, F. A.; Onyemekonwu, R. C.; Giweze, E. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study examined Co-operators' perception towards cooperatives' involvement in agricultural extension delivery. Multi-stage sampling process was used to select 337 respondents sampled through the use of questionnaires. Descriptive statistical tools were used to analyse data collected while Logit regression was used to analyze the hypothesis. The results showed that 93.2% of the co-operators had a positive attitude towards cooperatives' involvement in extension delivery, while only 6.8% did not. The likelihood ratio or model chi-square was significant (chi-square = 95.49; df = 8; P<0.050) which indicated that the independent variables had a significant influence on co-operators’ perception of the involvement of cooperatives in agricultural extension delivery. Based on the result, educational qualification (b=-1.274), farming experience (b=-0.601), income (b=1.065), cooperative experience (b=-0.620) and co-operators attitude (b=-0.191) had a significant relationship with the co-operators perception towards cooperative involvement in extension service delivery. It was concluded that most co-operators have a positive perception toward cooperative involvement in extension service delivery; hence they are willing to accept extension programmes channelled through cooperative societies. The researchers recommended that co-operators should be trained to build their capacity in rendering extension services.